Energy productivity of Indian agriculture: are energy guzzling districts generating higher agricultural value? - Rajan, Abhishek; Ghosh, Kuhelika (2019)
Groundwater irrigation has been central to India’s irrigated agriculture. India is the largest extractor of groundwater, pumping nearly 250 km3 every year for irrigation. The abstraction of groundwater is closely coupled with access to subsidized or free electricity in the country. Supply of free electricity has led to the perverse groundwater-energy nexus in the country. This nexus has resulted in grave economic and environmental repercussions. There is a mounting fiscal burden of energy subsidies in the country, which has led many power utilities at the helm of bankruptcy. At the same time, free power has attributed to the groundwater depletion at an alarming rate in many parts of the country. Hence, it becomes important to understand whether these economic and environmental costs of groundwater irrigation are commensurate with its benefits. This study takes a look at the energy productivity of groundwater irrigated agriculture in the districts of India and assesses its contribution to the agricultural output.